History of Soviet Architecture as Seen from Mid-Century Leningrad: On the Diversity of Historiographical Perspectives - Bass, Vadim G. (Actual Problems of Theory and History of Art, 2024)
During the 1930s to the 1950s the Academy of Architecture of the USSR developed several projects on the history of Russian and Soviet architecture. By the turn of the 1940s and 1950s, some of them reached the manuscript stage and became the subject of reviewing and professional discussion. These discussions demonstrated impressive variety of opinions. Along with the “All-Union” (Moscow-centric) perspectives, there were also “local” ones. Despite the centralization and ideological constraints, the Leningrad architectural community retained a certain degree of autonomy in terms of both style and values. The article has been based on archival documents including the discussions of the ‘Concise Course of the History of Soviet Architecture’ at the Leningrad branch of the Academy. They allow to reconstruct a peculiar “Leningrad perspective” on the Soviet history of architecture. A certain autonomy of the Leningrad architecture was reflected in the view that the city was practically unaffected by “formalist” and modernist trends, in the assertion of professional continuity in relation to the works of the masters of the pre-revolutionary period, in the constant emphasizing of the city-planning and ensemble qualities that underlie the local tradition, and, finally, in the selection of monuments and personalities to whom separate essays should be devoted in the course.
Keywords: history of Soviet architecture; Leningrad architectural school; the course of the architectural history; the Academy of Architecture of the USSR; local trends in Soviet architecture